Understanding China's Belt and Road Initiative - Yu, Hong (Asia in Transition, 2024)
This open access book provokes critical thinking regarding the most ambitious Chinese project since the founding of the People's Republic of China, The Belt and Road Initiative (BRI). The book presents extensive quality research and original insights in assessing the status of China's outbound investment and construction projects under the BRI umbrella. Referring to case studies and projects of selected countries from Southeast Asia, Central Asia, and the Middle East, the author sheds new light on the issues and problems associated with the BRI's implementation and discusses both the readjustments and prospects for the BRI. Finally, this book demarcates the limits and potential of the world's second largest economy in pushing for the BRI, which is challenged by enormous domestic tensions and external pressures. It also identifies and analyzes potential new collaboration areas between the Belt and Road countries and China under the BRI framework in the context of the post-COVID-19 era. It provides an outstanding reference for academics, students, policymakers, and the business community working in areas of international affairs and Asian economics and development, particularly those interested in Sino-relations and Chinese power dynamics in the global world order.